2007
DOI: 10.1016/j.ejcts.2007.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular outflow tract obstruction after arterial switch operation for the Taussig–Bing heart☆

Abstract: Postoperative right-sided obstruction occurs more frequently after ASO repair of Taussig-Bing heart than after TGA arterial switching, leading to higher reintervention rate. Resection of the commonly associated subaortic stenosis often prevents RVOTO development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 11 publications
2
21
0
Order By: Relevance
“…In the literature, several preoperative anatomic indicators have been identified as risk factors for reinterventions, such as aortic arch obstruction, preoperative subaortic RVOTO, side-by-side arteries, and PA to aorta mismatch. 12,21 In our experience, similar to that of Comas and colleagues, 22 the reintervention rate was higher in patients with arch obstruction.…”
Section: Risk Factors For Reinterventionsupporting
confidence: 84%
“…In the literature, several preoperative anatomic indicators have been identified as risk factors for reinterventions, such as aortic arch obstruction, preoperative subaortic RVOTO, side-by-side arteries, and PA to aorta mismatch. 12,21 In our experience, similar to that of Comas and colleagues, 22 the reintervention rate was higher in patients with arch obstruction.…”
Section: Risk Factors For Reinterventionsupporting
confidence: 84%
“…This situation can produce postoperative neopulmonary valvar stenosis and right ventricular outflow obstruction [ 6 , 12 ]. Moreover, the anatomic factors that have previously been reported to be related to the occurrence of subneopulmonary stenosis are associated with AAO, coronary anomalies, side-by-side great artery relationships and the preoperative presence of organic subaortic stenosis [ 15 ]. However, Soszyn et al [ 16 ] reported that there were no significant risk factors in their study.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9]13,17] Reintervention was observed mostly within the first one or two years, as in this cohort. [9,12,21] Right ventricular outflow tract obstruction was observed up to 9 to 10 years after arterial switch operation for transposition of the great arteries. [22,23] The number of patients under follow-up up to 9 to 10 years after arterial switch operation for Taussig-Bing anomaly is limited both in this cohort and in the literature; therefore, whether a higher number of reintervention is to be expected in the years to come still remains unknown.…”
Section: Discussionmentioning
confidence: 99%